2012
DOI: 10.1590/s1806-66902012000200024
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidas no alto rio Poxim, Sergipe e os riscos de contaminação dos recursos hídricos

Abstract: Resumo -A crescente atividade agrícola em áreas de mananciais tem causado preocupações quanto à contaminação por herbicidas em áreas agrícolas. O problema se torna mais importante quando a contaminação pode afetar a água para uso humano, como ocorre com a água do Rio Poxim, que abastece a cidade de Aracaju, capital do Estado de Sergipe. O objetivo do estudo foi avaliar o risco de contaminação de águas superficiais e subterrâneas por herbicidas no alto da Sub-bacia do Rio Poxim e detectar a presença dos princíp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 20 publications
1
14
0
5
Order By: Relevance
“…Consequently, their residues were found along all the collection points, from IP01 to IP08. Similar results were reported by Britto et al (2012), who observed the presence of Diuron and Ametryn in the water from the Poxim River, Sergipe, at levels that varied from 0.03 to 0.9 and 0.03 to 0.5 µg L -1 , respectively. Muendo et al (2012) also investigated the presence of herbicides in areas of sugarcane cultivation bordered by the Kuywa River, in Kenya, and observed Diuron levels varying from 0.44 to 1.75 µg L -1 .…”
Section: Resultssupporting
confidence: 90%
“…Consequently, their residues were found along all the collection points, from IP01 to IP08. Similar results were reported by Britto et al (2012), who observed the presence of Diuron and Ametryn in the water from the Poxim River, Sergipe, at levels that varied from 0.03 to 0.9 and 0.03 to 0.5 µg L -1 , respectively. Muendo et al (2012) also investigated the presence of herbicides in areas of sugarcane cultivation bordered by the Kuywa River, in Kenya, and observed Diuron levels varying from 0.44 to 1.75 µg L -1 .…”
Section: Resultssupporting
confidence: 90%
“…The use of pesticides, especially herbicides, has been promoting environmental and food contamination, people poisoning and problems associated with agricultural practices such as intoxication of further crops and emergence of herbicide-resistant weeds (BRITTO et al, 2012;NEVES;BELINI, 2013). Even so, literature reports concerning biodiversity impacts on surrounding areas are still scarce, especially on wind-drifted agrochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Glyphosate residues have been found in surface waters (Dores & Freire, 2001;Silva et al, 2003;Queiroz et al, 2011), in groundwater (Sakaliene et al, 2007;Andrade et al, 2011;Britto et al, 2011), and in soil Souza et al, 2006).…”
Section: Introductionmentioning
confidence: 99%